2008
DOI: 10.1097/psy.0b013e31816ffc39
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Somatization in General Population

Abstract: This was the first time the independent association between alexithymia and somatization was established in a large, nationally representative nonclinical sample of both young and old adults with and without mental disorders and somatic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
151
2
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(183 citation statements)
references
References 60 publications
15
151
2
15
Order By: Relevance
“…The mean scores of the SCM SOM scale for a community sample of the Finnish population in a study by Holi et al (28) were clearly lower than those of our patients, and in an outpatient sample of psychiatric Finnish patients the scores were higher. Higher SCL SOM scores (38), as well as higher hypochondria scores (39), have been shown to be associated with female gender, and females were overrepresented in our material. Similarly, there is an association with somatic diagnoses (38), as all of the symptoms on the SCL SOM scale may be reflections of a physical illness.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The mean scores of the SCM SOM scale for a community sample of the Finnish population in a study by Holi et al (28) were clearly lower than those of our patients, and in an outpatient sample of psychiatric Finnish patients the scores were higher. Higher SCL SOM scores (38), as well as higher hypochondria scores (39), have been shown to be associated with female gender, and females were overrepresented in our material. Similarly, there is an association with somatic diagnoses (38), as all of the symptoms on the SCL SOM scale may be reflections of a physical illness.…”
Section: Discussionsupporting
confidence: 53%
“…Higher SCL SOM scores (38), as well as higher hypochondria scores (39), have been shown to be associated with female gender, and females were overrepresented in our material. Similarly, there is an association with somatic diagnoses (38), as all of the symptoms on the SCL SOM scale may be reflections of a physical illness. Our results did not point to any greater degree of somatization among our OA patients compared to the other groups.…”
Section: Discussionsupporting
confidence: 53%
“…Consequently, it is claimed that these patients express psychological stress alternatively through somatization (2). In fact, many epidemiological and clinical studies have demonstrated a significant association between alexithymia and somatic symptom reporting, and it was suggested that alexithymia was a potential factor inthe somatization (15,36,37). A study conducted in our country reported that childhood trauma rates were higher in patients with depression accompanied with alexithymia and that alexithymia contributed to the emergence of somatic symptoms in depression (16).…”
Section: Discussionmentioning
confidence: 95%
“…Une grande partie des études provient des pays scandinaves ; elles situent la prévalence aux alentours de 10 % (Salminen, 1999 ;Honkalampi, 2000 ;Honkalampi, 2004 ;Matilla, 2006 ;Mattila , 2008). Ce chiffre de 10 % est le plus souvent retenu dans la littérature.…”
Section: Fréquence Et Populations Concernéesunclassified
“…La fréquence de l'alexithymie est associée au sexe masculin, aux âges avancés, au faible niveau d'éducation ou de revenus, aux statuts peu valorisants, à l'isolement social, aux conditions défavorisées dans l'enfance (Kauhanen, 1993 ;Salminen, 1999 ;Mattila, 2006), à la condition de chômeur (Kauhanen, 1993) ou d'ouvrier (Honkalampi, 2004). (Badura, 2003 ;Wang, 2011), dépression (Honkalampi, 2000 ;Kojima, 2003 ;Honkalampi, 2004 ;Lipsanen, 2004 ;Wang, 2011), burnout (Mattilla, 2007, troubles somatoformes (Sayar, 2001 ;De Gucht, 2003 ;Waller, 2004 ;Mattila, 2008), hypertension artérielle (Todarello, 1995), psoriasis (Richards, 2005 ;Willemsen, 2008 ;Masmoudi, 2009), alopécie, dermite atopique, vitiligo et urticaire chronique (Willemsen, 2008), douleurs non spécifiques de l'épaule, sans signes objectifs à l'examen (Miranda, 2005), plaintes somatiques (Halpern, 2012).…”
Section: Fréquence Et Populations Concernéesunclassified